2019
DOI: 10.1371/journal.pone.0226187
|View full text |Cite
|
Sign up to set email alerts
|

Nexrutine and exercise similarly prevent high grade prostate tumors in transgenic mouse model

Abstract: The purpose of this investigation was to compare the antitumorigenic effects of the natural product Nexrutine to voluntary wheel running (VWR) in the transgenic adenocarcinoma of the mouse prostate (TRAMP) model. Forty-five, 10-week old TRAMP mice were randomized to either receive free access to the running wheel, Nexrutine pelleted into chow at 600 mg/kg or no treatment control. Mice were serially sacrificed at weeks 4, 8,12 and 20 weeks. Palpable tumors, body weight, food consumption and running wheel activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Despite challenges of COVID-19 restrictions, 9 participants in the intervention group and 6 participants in the control group completed the study. Although not statistically significant, a decrease across all biomarkers followed the same trend previously seen in the murine exercise study in our laboratory, 34 lending support for the translational nature of our intervention to the clinical population. Our results are similar to findings of a home-based exercise intervention by Hvid et al 24 who observed a non-statistically significant decrease in mean IL-6 after 24 months; however, this study found an increase TNF-α within the same time parameters.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Despite challenges of COVID-19 restrictions, 9 participants in the intervention group and 6 participants in the control group completed the study. Although not statistically significant, a decrease across all biomarkers followed the same trend previously seen in the murine exercise study in our laboratory, 34 lending support for the translational nature of our intervention to the clinical population. Our results are similar to findings of a home-based exercise intervention by Hvid et al 24 who observed a non-statistically significant decrease in mean IL-6 after 24 months; however, this study found an increase TNF-α within the same time parameters.…”
Section: Discussionsupporting
confidence: 78%
“…2,10,11 Work within our laboratory has demonstrated shifts in circulating cytokines in response to exercise in preclinical studies. (34) 12 Specifically, our group noted that up to 20 weeks of voluntary wheel running significantly reduced the progression to high-risk tumors in transgenic prostate tumor challenged mouse models. This reduction in tumor progression was associated with significant decreases in pro-inflammatory cytokines, such as eotaxin, interleukin (IL)-1a, IL-5, IL-12 (p40) and VEGF.…”
Section: Introductionmentioning
confidence: 97%
“…IFN-γ has been found in different studies to have protective effects on tumor growth and suggestive of a strong immune response [ 41 ]. Specifically, low serum IFN-γ levels have been inversely associated with tumor stage [ 42 ] and tumor size [ 43 ] though the specific mechanism attributed to this benefit is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are large disparities between studies, with some reporting no effect or even increased tumor growth in response to physical activity. In PCa more specifically, some studies reported slower tumor growth with physical activity [ 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], while others found no effect [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. McCullough et al even reported that while TR had no effect on tumor weight in immunocompetent Copenhagen rats, it significantly increased tumor weight in nude rats [ 28 ].…”
Section: Discussionmentioning
confidence: 99%